2021
DOI: 10.1186/s13011-021-00382-x
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing and its associated factors among street-based female sex workers in Iran: results of a national rapid assessment and response survey

Abstract: Background Female sex workers (FSWs) are at a disproportionate risk of sexually transmitted infections and they may face significant barriers to HIV testing. This study aimed to examine HIV testing prevalence and its associated factors among street-based FSWs in Iran. Method A total of 898 FSWs were recruited from 414 venues across 19 major cities in Iran between October 2016 and March 2017. Eligible FSWs were women aged 18 years of age who had at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…These findings align with results from studies conducted in Iran, China and Uganda where only 57.8%, 68.3% and 56% of FSWs had tested for HIV [15][16][17]. Furthermore, in Canada, approximately 57.9% of FSWs tested for HIV and /or STIs with 45.5% and 44.9% of FSWs reported HIV and STI testing respectively and only 32.6% reported screening for both [18].…”
Section: Discussionsupporting
confidence: 86%
“…These findings align with results from studies conducted in Iran, China and Uganda where only 57.8%, 68.3% and 56% of FSWs had tested for HIV [15][16][17]. Furthermore, in Canada, approximately 57.9% of FSWs tested for HIV and /or STIs with 45.5% and 44.9% of FSWs reported HIV and STI testing respectively and only 32.6% reported screening for both [18].…”
Section: Discussionsupporting
confidence: 86%
“…We found that HIV testing dropped significantly among FSWs in 2020 compared to the 70.1% reported for 2015 [ 9 ]. The results of another study among FSWs in 2017 reported that about half of FSWs tested for HIV in a lifetime [ 10 ]. Some of these differences may be due to the different sampling methods for recruiting participants in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…There is a big gap between the current HIV diagnosis rates in Iran [4,9,10] and the UNAIDS 95-95-95 targets for HIV diagnosis [9]. HIV testing can be associated with HIV risk perception, awareness of HIV test, age at sex work initiation, receiving free-of-charge harm reduction services, unstable housing, drug use, the level of income, incarceration history, having paying and non-paying partners, and knowing an HIV testing site [4,[9][10][11]. The HIV testing uptake was 70.1% among (FSWs) in Iran in 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the prevalence of HIV-positive among FSWs in 50 low-income countries was 11.8%, which was higher than the prevalence found in the present study. In the study by Ahmadi et al, 57.8% (95% CI: 20–88) of participants reported being tested for HIV, and HIV prevalence among FSWs who were tested for HIV was 10.3% (95% CI: 7.5–13) [ 22 ]. In the Netherlands, an overall HIV prevalence of 3.8% was reported, but this was significantly higher among women with a history of injecting drug use (13.6%) than among women without drug use (1.5%) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are highly vulnerable to HIV infection because they engage in risky behaviors such as multiple sexual partners, high prevalence of other sexually transmitted infections (STIs), high use of injectable or non-injectable drug use, inconsistent condom use, or non-use during sexual contact, etc. [ 4 , 5 ]. In a 2019 meta-analysis, 37 eligible original articles published between 2010 and 2017 reported HIV prevalence at 2.17% in 46,657 FSWs.…”
Section: Introductionmentioning
confidence: 99%